Analysis of Performance Management, Loyalty and Image of the Head of the Hotel Service towards the Perception of the Tomini Bay Community in the Framework of Strengthening the Maritime Area of Gorontalo Province - Djafri, Novianty; Wolok, Tineke; Franssisca, Meriyana (PPSDP International Journal of Education, 2024)
The aim of this research is to analyze hotel performance management in the context of hotel business management loyalty and the image of the hotel manager towards the perception of the people of the Tomini Bay area to strengthen the maritime region in Gorontalo province. The benefit of this research is to analyze the consistency of hotel management performance, including leadership and employees with hotel business management loyalty and the image of the head of hotel on the perception of the people of the Tomini Bay area to strengthen the maritime region in Gorontalo province. This is survey research with a mixed method approach, combining qualitative interviews with hotel leaders and quantitative analysis of employee performance data and perceptions of hotel users (consumers). The results conclude the importance of the results of appropriate leadership performance management analysis and increasingly implementing proactive and productive strategies for hotel business management loyalty in facing challenges, maintain high performance, and ensure long-term success in the hotel industry to maintain the image of the hotel business towards improving the public perception of the Tomini Bay area to strengthen the maritime region in Gorontalo province.